2019
DOI: 10.1371/journal.pone.0204185
|View full text |Cite
|
Sign up to set email alerts
|

Intra-athlete and inter-group comparisons: Running pace and step characteristics of elite athletes in the 400-m hurdles

Abstract: The aim of this study was to investigate the running pace and step characteristics among various competitive-level 400-m hurdlers through inter-group and intra-athlete comparisons. We analysed spatiotemporal data involving the split time, mean step length (SL) and mean step frequency (SF) for 13 male world-class and 14 male national-level 400-m hurdlers. We analysed 16.5 ± 3.9 races for each world-class hurdler and 19.8 ± 6.0 races for each national-level hurdler (the total number of analysed runs was 491) usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…These results support the evidence from previous studies [21,30], who also observed a significant increase in contact time and a decrease in running speeds for 400-m sprints. Note that the average and SD of step frequency measured in this study (3.52 ± 0.19) are comparable with those of national-level hurdlers presented in [28]. We also observed that the step frequency significantly decreased starting from the third interval.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results support the evidence from previous studies [21,30], who also observed a significant increase in contact time and a decrease in running speeds for 400-m sprints. Note that the average and SD of step frequency measured in this study (3.52 ± 0.19) are comparable with those of national-level hurdlers presented in [28]. We also observed that the step frequency significantly decreased starting from the third interval.…”
Section: Discussionsupporting
confidence: 86%
“…As one of the goals of this study was to provide feedback to the participants and trainers, we extracted key performance features from the races [27,28], such as contact time (CT), flight time (FLY), step frequency (STF) and speed (SPE). Moreover, we obtained the speed using the distance between the hurdles (D H ) and the time difference between two consecutive HC.…”
Section: Discussionmentioning
confidence: 99%
“…Cooper (1966) , the silver medalist of the 1964 Games, identifies the so-called “coasts” (instants marked by stabilization of the pace) and “kicks” (rapid acceleration) as elements that play decisive roles in the competition ( Cooper, 1966 ). After the introduction of synthetic tracks, basic elements of temporal structure (“split times”) and spatial structure (“stride pattern”) provided interesting insights for scientific analysis ( Ditroilo and Marini, 2000 ; Guex 2012 ; Otsuka and Isaka, 2019 ). Changes in stride variables in different parts of the distance impact the strategy of hurdle races ( Martens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a 400 m hurdles race, athletes using one attack leg cover the distance using a “rhythm” (i.e., a stride pattern) with 13.15 (men) or 17 steps (women) [ 16 , 20 ]. Due to increasing fatigue, the running step is shortened, and competitors are forced to increase the number of steps (e.g., from 13 to 14) and thus to change the trail leg, e.g., from right to left [ 6 , 19 , 32 , 33 ]. The authors of the training textbooks noted significant differences between the training of athletes with only “one leg” and those who attack hurdles with both their left and right legs [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%